HEALTH BEHAVIOR AND DENTAL CARRIES IN COASTAL COMMUNITY: LITERATURE REVIEW - Komarudin, Koko; Apriasari, Maharani Laillyza; Azizah, Aulia (Odonto : Dental Journal, 2021)
ABSTRACTBackground: The important role of coastal communities is not directly in line with their living conditions, which are mostly poor. Dental caries is basically a disease that is also suffered by the general public in Indonesia, even in the world. RISKESDAS 2018 shows the prevalence of caries in Indonesia is 88.8%. Dental caries is caused by the bacterium Streptococcus mutans. People who live in coastal areas are at risk of suffering from dental caries. Brushing behavior also has a relationship with the incidence of dental caries. Method: All articles reviewed were obtained from Pubmed, Science Direct, and Google Scholar with a period of 10 years in full text. using the keywords behavior, caries, and coastal area.Result: Based on reviews from several journals, it was found that the brushing behavior of coastal communities was good, but the frequency of brushing teeth was not appropriate and the behavior of using drinking water had no known fluoride content. There are variations in the category of dental caries at the age level of people in coastal areas.Conclusion: Knowledge and healthy behavior can reduce the risk of dental caries related to the behavior of coastal communities, so that life productivity can be much better than ever.